Determinant Of MSMEs Actors' Interest in Applying for Halal Certification (Towards Halal Mandatory 2024) - Effasa, Ahmad Saifurriza; Rochmayanti, Dewi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In UUD No.33 of 2014, it is explained that the halal certification decision